2016
DOI: 10.3329/pa.v27i2.29322
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moringa leaf extract on growth and yield of maize

Abstract: The present study was conducted in the Soil Science Field Laboratory at Bangladesh Agricultural University, Mymensingh during November 2014 to April 2015 to study the effect of moringa leaf extract on growth and yield of maize. The experiment comprised of five treatments viz., T1 (control), T2 (water sprayed at every 2 weeks, starting from 2 weeks after emergence), T3 (moringa leaf extract sprayed at 2 weeks after emergence), T4 (moringa leaf extract sprayed at 2 and 4 weeks after emergence) and T5 (moringa le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 9 publications
(6 reference statements)
4
14
2
Order By: Relevance
“…This is in agreement with the findings of Taha (2015) who reported that exogenous application of MLE with 10 % concentration increased the plant height of the Jojoba plant. In contrast, foliar application of MLE at 1:32 concentration increased the plant height in maize (Biswas et al, 2016), tomato (Culver et al, 2012), beans and maize (Mvumi et al, 2013). This might be due to zeatin, which is the most common cytokinin in the extract, responsible for the improved plant height.…”
Section: Preparation Of Moringa Leaf Extract and Applicationmentioning
confidence: 99%
“…This is in agreement with the findings of Taha (2015) who reported that exogenous application of MLE with 10 % concentration increased the plant height of the Jojoba plant. In contrast, foliar application of MLE at 1:32 concentration increased the plant height in maize (Biswas et al, 2016), tomato (Culver et al, 2012), beans and maize (Mvumi et al, 2013). This might be due to zeatin, which is the most common cytokinin in the extract, responsible for the improved plant height.…”
Section: Preparation Of Moringa Leaf Extract and Applicationmentioning
confidence: 99%
“…Non-judicious use of chemical fertilizers seldom ensures product quality and creates environmental issues as well [Mattner et al 2013]. Growers are mindful now regarding organic fertilizer for increasing yield and quality [Biswas et al 2016]. Bio-stimulants reduce fertilizers requirement consequently less environment degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Moringa oleifera Lam. belongs to family Moringaceae is a miracle tree in agriculture [Moyo et al 2011, Biswas et al 2016. The plant is native to sub-Himalayan tracts of Pakistan, Afghanistan, Bangladesh and India [Fahey 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Leaf extracts can stimulate plant growth and increase crop yield. For instance, application of Moringa leaf extract at 2 weeks after emergence and at every 2 weeks thereafter, significantly increased growth performances of maize in terms of plant height, shoot length, fresh and dry weight of shoots, number of grains cob -1 , 100-grain weight, and grain weight plant -1 (Biswas et al, 2016).…”
Section: Medicinal Usesmentioning
confidence: 99%